A survey on playing-related musculoskeletal disorders among classical piano students of tertiary institutions in Malaysia - Ling, Chia Ying; Loo, Fung Chiat; Hamedon, Titi Rahmawati (2016)
Musicians are at risk of playing-related musculoskeletal disorders (PRMD) with incidence ranging from approximately 30% to 90% in the shoulder-arm-hand region and within the spine. Pianists are one of the high risk groups of PRMD due to the nature of playing posture and practice habits. The number of pianists in Malaysia has increased significantly due to the growth of music programmes in tertiary institutions. Although extensive research has been carried out into PRMD for decades, investigation of PRMD among pianists in Malaysia is very limited. This paper aimed to identify the extent of PRMD occurring among classical piano students in tertiary institutions in Malaysia. A survey was conducted and 192 set of data collected through administration of a questionnaire. Results showed that 35.8% (68) students reported having PRMD, of whom 17.6% were male (12) and 82.4% (56) were female. There is a great necessity to introduce ways to prevent PRMD which was reported at various levels among classical piano students.